Bioluminescent detection of isothermal DNA amplification in microfluidic generated droplets and artificial cells - Hardinge, Patrick (Sci Rep, 2020)
Microfluidic droplet generation affords precise, low volume, high throughput opportunities for molecular diagnostics. Isothermal DNA amplification with bioluminescent detection is a fast, low-cost, highly specific molecular diagnostic technique that is triggerable by temperature. Combining loop-mediated isothermal nucleic acid amplification (LAMP) and bioluminescent assay in real time (BART), with droplet microfluidics, should enable high-throughput, low copy, sequence-specific DNA detection by simple light emission. Stable, uniform LAMP–BART droplets are generated with low cost equipment. The composition and scale of these droplets are controllable and the bioluminescent output during DNA amplification can be imaged and quantified. Furthermore these droplets are readily incorporated into encapsulated droplet interface bilayers (eDIBs), or artificial cells, and the bioluminescence tracked in real time for accurate quantification off chip. Microfluidic LAMP–BART droplets with high stability and uniformity of scale coupled with high throughput and low cost generation are suited to digital DNA quantification at low template concentrations and volumes, where multiple measurement partitions are required. The triggerable reaction in the core of eDIBs can be used to study the interrelationship of the droplets with the environment and also used for more complex chemical processing via a self-contained network of droplets, paving the way for smart soft-matter diagnostics.